ISLAMIC BRAND ANALYSIS ON RETAIL USING BRAND CANVAS MODEL - Achmad Ihya Ulumuddin; Hamidah Tussifah (Islamic Business and Management Journal, 2018)
The growth of the world's Muslim population today has greatly affected the governance in the daily life of people in different parts of the world. It has attracted the attention of some observers in the business unit sector. Particularly companies that will target Muslim share. It is clear that if the awareness of Halal and Haram increases, then the equity of Islamic brands will also be affected. Islamic values in the brand can be through several ways, including: based on aspects of compliance, based on its origin, based on the consumer. The purpose of this research is to find out how the points of Islamic brand can be implemented by LaTansa Gontor Department Store along with a good strategy identification. This research used qualitative method with grounded theory. The data were collected using observation, interview and documentation techniques. Determination of sample used by the researcher is purposive sampling, while data analysis method used is a method of Miles and Hubberman with Brand Canvas as an instrument. From this research, it can be concluded that LaTansa Gontor Department Store has succeeded in infusing its brand image into the minds of their customers. LaTansa Gontor logo is considered to be less able to inform its brand. The research also found that application of Islamic values based on the aspect of compliance is on the name, promise, character, and sales. Based on the origin, it can be reviewed from the name, position statement, color, logo, and text. Based on consumers, it can be reviewed from the persona and basic story of the brand.